Sosialisasi Pendampingan Asupan Gizi Atlet Muda di Kota Palangka Raya pada Masa Pandemi Covid-19 - Yudo Harvianto; Nune Wire Panji Sakti (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
For an athlete to get a complete nutritional intake with the right portion of food, will make the athlete's body can function to the maximum, so that performance will also be maximal when doing competitions. Therefore, it is important for an athlete to really attention to his nutritional intake, especially the balance between nutritional intake and energy expenditure, both in the phase before, during, and after a match or exercise. Because energy will affect the performance of athletes, as well as the maximum performance of athletes will support it to achieve the best achievement. Especially with the current covid-19 outbreak. The purpose of this dedication is that athletes can find their best diet to improve the efficiency of the body's metabolism to face exercise and matches. The method carried out in this activity is socialization. The implementation of this activity is conducted face-to-face.Participants in this activity are young athletes who are in the city of Palangka Raya with a total of 15 people from various sports including badminton, soccer, volleyball, athletics (sprint), athletics (fast walking), athletics (reject bullets), table tennis, karate, sepak sawut. Based on the results obtained from this activity, there are several problems including the knowledge of athletes about the importance of setting the nutritional intake of sports is still relatively low, the lack of varied food menu consumed, the use of supplements by athletes are too excessive.  Then after being able to know about the problem, the presenter gave direction to the athletes to be able to minimize the problem.After the implementation of this activity, the athletes get education regarding nutrition assistance, maximizing the performance of athletes through a diet that suits nutritional needs.As well as education and solutions related to improved performance. The conclusion of this activity is to provide education on nutrition assistance for young athletes in Palangka Raya City.